Analisa Pelanggaran Etika Pariwara Pada Iklan Youtube “Garnier Bright Complete 3% Ampoule Serum” - Ramadhan, Fadhilah Medy Putra; Hilal, Hilal; Pahlevi, Muhammad Reza (PT Literasi Nusantara Publisher, 2024)
Brand image or a brand personality is important for a brand in the communication process. It is also important for consumers to identify brands. This Image Brand is also carried out by Garnier as a treatment brand for dull skin in the problem of skin hyperpigmentation which is often a skin problem for women in Indonesia. Garnier creates advertisements as a form of communication regarding the innovation of the Ampoule Serum product. Research on the Analysis of Violations of Advertising Ethics was carried out on Garnier's Youtube Ad